A way to more effective education : prospective teachers' interest in service-learning - Modić Stanke, Koraljka (Array, 2019)
To become a teacher one must possess a minimum of pedagogical competences, obtained by the completion of pedagogical-psychological-didactic-methodical education. It is assumed that it will be followed by professional growth in the foreseeable future – but that does not necessarily happen. One way to provide a better head start for prospective teachers and their future students is to implement a service-learning (S-L) – a pedagogical approach that combines academic coursework with voluntary service in the community. The aim of this study is to determine the initial interest of students for engaging in service-learning within compulsory courses of pedagogical-psychological-didactic-methodical education and to investigate the relationship between the level of service-learning information and the reported interest in service-learning. Participants were 42 graduate students, divided into two groups – experimental (attended a lecture on service-learning between measurements) and control group (no intervention between two measurements). Results demonstrate high(est) interest for service learning within the course Psychology of Education. Prospective teachers that attended the lecture on service-learning became more interested in it. Most of the students think that engaging in service-learning would lead to higher motivation and better knowledge of the course. These findings should encourage teachers and policy-makers to consider the implementation of S-L in educational institutions in order to improve educational efficiency on all levels of the educational system.